Radiosensitizing potential of Plumbagin in B16F1 melanoma tumor cells through mitochondrial mediated programmed cell death - Rao, Bola Sadashiva Satish; Kumar, Mandala Rayabandla Sunil; Das, Shubhankar; Aithal, Kiran; Udupa, Nayanabhirama (Journal of Applied Biomedicine, 2015)
The radiosensitizing potential of Plumbagin (PLB) against chemo- and radioresistant B16F1 melanoma cells growing in vitro was investigated. Clonogenic assay revealed a sensitization enhancement ratio (SER) of 1.5 for PLB treatment in combination with radiation. PLB pretreatment for 1 h prior to radiation resulted in elevated intracellular ROS levels compared to the group treated with radiation alone. Alkaline comet assay analysis revealed PLB's potential to enhance the radiation induced DNA damage. Cell cycle studies have shown enhanced G2/M arrest for combination treatment of PLB with radiation. Cell death exerted by PLB combination was mainly through programmed cell death, involving the depletion of mitochondrial membrane potential, increase in the expression of p53, Bax, Cytochrome c, PARP and Caspase 3 cleavage. In conclusion, this study demonstrates the radiosensitizing potential of PLB to inhibit the growth of melanoma cells in vitro, which may be attributed to the oxidative stress and DNA damage leading to enhanced mitochondria-mediated programmed cell death. Also, this study demonstrate the ability of PLB to augment ionizing radiation induced tumor cell kill which further warrant the avenue for the development of a clinically useful radiosensitizer.
Keywords: bcl-2-Associated X Protein; In Vitro Techniques; melanom; Cytochromes c; chemoradioterapie; techniky in vitro; plumbagin; mitochondriální membrány; Melanoma; Mice; zvířata; chemorezistence; oxidační stres; fytogenní protinádorové látky; Mitochondrial Membranes; superoxidy; Antineoplastic Agents, Phytogenic; Naphthoquinones; cytochromy c; apoptóza; Tumor Suppressor Protein p53; intracelulární membrány; poškození DNA; Intracellular Membranes; Caspase 3; DNA Damage; Chemoradiotherapy; Plumbaginaceae; adjuvancia imunologická; naftochinony; nádorový supresorový protein p53; Poly(ADP-ribose) Polymerase Inhibitors; Oxidative Stress; Drug Resistance, Neoplasm; Radiation-Sensitizing Agents; protein X asociovaný s bcl-2; myši; PARP inhibitory; Animals; Superoxides; radiosenzibilizující látky; Adjuvants, Immunologic; kaspasa 3; Apoptosis